2013
DOI: 10.1007/s00534-013-0606-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of pancreaticobiliary maljunction: update analysis of 2nd Japan‐nationwide survey

Abstract: Introduction Pancreaticobiliary maljunction (PBM) is a congenital anomaly, which can be defined as a union of the pancreatic and biliary ducts located outside off the duodenal wall. We herein investigate clinical features of PBM including as the 2nd report of a Japanese nationwide survey.Patients and methods During a period of 18 years (from 1990 to 2007), 2,561 patients with PBM were registered at 141 medical institutions in Japan. Among them, eligible patients (n = 2,529) were divided into two groups: adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 14 publications
7
124
2
1
Order By: Relevance
“…The ratio of gallstone detection in PBM patients who developed gallbladder cancer was lower than that in the biliary cancer population without PBM [2,3,32]. In our series, the ratios were 10 % and 62 %, respectively [1].…”
Section: Incidence and Characteristicscontrasting
confidence: 52%
See 3 more Smart Citations
“…The ratio of gallstone detection in PBM patients who developed gallbladder cancer was lower than that in the biliary cancer population without PBM [2,3,32]. In our series, the ratios were 10 % and 62 %, respectively [1].…”
Section: Incidence and Characteristicscontrasting
confidence: 52%
“…According to a nationwide survey in Fig. 1 The pathophysiology of pancreaticobiliary maljunction [3] Japan (n = 2561) [2], biliary cancer was detected in 21.6 % of adult patients with congenital biliary dilatation and in 42.4 % of PBM patients without biliary dilatation. In patients with biliary cancers in association with PBM, the location ratio of cancers in the bile duct and gallbladder were 32.1 % and 62.3 % in congenital biliary dilatation, and 7.3 % and 88.1 % in PBM patients without biliary dilatation, respectively.…”
Section: Incidence and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Japanese retrospective nationwide survey of PBM revealed that the incidence of biliary tract cancers was 21.6% in the group with bile duct dilatation; 13.4% were gallbladder carcinoma, 7.0% were bile duct carcinoma, and 1.0% were both gallbladder and bile duct carcinomas [20]. According to the result and other reports, the prophylactic excision of the gallbladder and common bile duct is the appropriate surgical procedure for PBM with bile duct dilatation [21].…”
Section: Prophylactic Treatmentmentioning
confidence: 96%